Early Experience and Emotional Development: The Emergence of Wariness of Heights - Campos, Joseph J.; Bertenthal, Bennett I.; Kermoian, Rosanne (Psychological Science, 1992)
Because of its biological adaptive value, wariness of heights is widely believed to be innate or under maturational control. In this report, we present evidence contrary to this hypothesis, and show the importance of locomotor experience for emotional development. Four studies bearing on this conclusion have shown that (1) when age is held constant, locomotor experience accounts for wariness of heights; (2) “artificial” experience locomoting in a walker generates evidence of wariness of heights; (3) an orthopedically handicapped infant tested longitudinally did not show wariness of heights so long as he had no locomotor experience; and (4) regardless of the age when infants begin to crawl, it is the duration of locomotor experience and not age that predicts avoidance of heights. These findings suggest that when infants begin to crawl, experiences generated by locomotion make possible the development of wariness of heights.